K2-60b and K2-107b: a Sub-Jovian and a Jovian Planet from the K2 Mission - Eigmüller, Philipp; Gandolfi, Davide (The astronomical journal, 2017)
We report the characterization and independent detection of K2-60b, as well as the detection and characterization of K2-107b, two transiting hot gaseous planets from the K2 space mission. We conﬁrm the planetary nature of the two systems and determine their fundamental parameters combining the K2 time-series data with FIESNOT and HARPS-N@TNG spectroscopic observations. K2-60b has a radius of 0.683±0.037 RJup and a mass of 0.426±0.037 MJup and orbits a G4 V star with an orbital period of 3.00267±0.00006days. K2-107b has a radius of 1.44±0.15 RJup and a mass of 0.84±0.08 MJup and orbits an F9 IV star every 3.31392±0.00002 days. K2-60b is among the few planets at the edge of the so-called “desert” of short-period sub-Jovian planets. K2107b is a highly inﬂated Jovian planet orbiting an evolved star about to leave the main sequence.